Gameplay-Supported Reflections on the Dialectics of Design Practice: Exploring Relations between Designers, Design Contexts, Design Processes and Designs by Means of Gameplay - SALL VESSELÉNYI, LÁSZLÓ (My University, 2019)
Design practice is anything but neutral. Designers, the various artifacts of design processes as well as overall design contexts carry values, assumptions and prioritizations about design-technical as well as socio-cultural issues of all kinds. The results of design practice, designs, are not neutral either, influencing the contexts they are created for and deployed in, beyond what they might have been explicitly designed for and beyond their intended effects on their circumstances. In addition, the biases of design practice have the potential to affect the actual designer, whether through elements of the design process or through the design context. These issues are of theoretical and practical importance to any designer, as they relate to questions of what can and cannot be designed (for) and what the consequences of design practice are. With this in mind, this thesis aims to explore how gameplay can be used to support reflection on these issues. To answer that question, this thesis in interaction design locates itself within the methodological frameworks of research through design and gameplay research and design. Beginning with a comprehensive material review including theoretical research and previous practical work, theoretical frameworks encompassing reflection, gameplay and the relations of design practice (i.e. those between designer, design context, design process and design) are identified. An iterative design process follows, where users are brought in early in ideation and where playtesting with users is a central component. The design process iterates over not only one but two parallel tracks of design game concepts exploring different approaches to the exploration. Ultimately, the result of the thesis is a board game titled Weapon of Criticism . Involving three to four players, the focus of the game is to win the game by occupying a certain proportion of the game board. The attempts at occupation are performed through deciding on a tile to occupy and then answering questions about design projects, questions which start with ones written on description, explanation and reflection cards and are developed into follow-up questions by other players. Through this design, Weapon of Criticism provides an answer to the research question of the thesis.
Keywords: interaction design; research through design; gameplay design; design game; reflection; reflective design; activity theory; human-artifact model